2008
DOI: 10.2337/dc07-2367
|View full text |Cite
|
Sign up to set email alerts
|

Use of the SINBAD Classification System and Score in Comparing Outcome of Foot Ulcer Management on Three Continents

Abstract: OBJECTIVE—To compare populations with and outcomes of diabetic foot ulcers managed in the U.K., Germany, Tanzania, and Pakistan and to explore the use of a new score of ulcer type in comparing outcomes among different countries. RESEARCH DESIGN AND METHODS—Data from a series of 449 patients with diabetic foot ulcers managed in the U.K. were used to evaluate the new simplified system of classification and to derive an aggregate score. The use of the score was then explored using data from series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
2
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(190 citation statements)
references
References 21 publications
(22 reference statements)
5
168
2
15
Order By: Relevance
“…The Condition of the DFU at First Expert Assessment Ulcers that are graded as being more severe have a worse prognosis, and this is the basis of current grading schemes (1,27,28). Recent data have also shown a statistically significant association between ulcer severity and the time to first expert assessment, in both Norway and the U.K. (29,30).…”
Section: Failure Of Dfus To Heal Promptlymentioning
confidence: 99%
“…The Condition of the DFU at First Expert Assessment Ulcers that are graded as being more severe have a worse prognosis, and this is the basis of current grading schemes (1,27,28). Recent data have also shown a statistically significant association between ulcer severity and the time to first expert assessment, in both Norway and the U.K. (29,30).…”
Section: Failure Of Dfus To Heal Promptlymentioning
confidence: 99%
“…[6][7][8] Paul, et al in a multicenter trial over three continents, found similar finding of mean age of 66.7 years. 9 Graham lee et al in a Scottish study reported a mean age of 67.4 years. 10 National hospital discharge survey, looking at 275,000 inpatient records from 500 hospitals since 1996 revealed that elderly diabetics had twice the risk of developing a foot ulcer, three times the risk of developing a foot abscess and four times the risk of developing Osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Diyabetik ayak ülserlerinin %70-90'ı ayağın ön kıs-mında görülür; sıklık sırasına göre topuk ve ayağın ortası bunu izler. [11] En sık kullanılan ülser sınıflandır-maları Wagner [17] , Brodsky [18] , University of Texas [19] , PEDIS [20] ve SINBAD [21] sınıflandırmalarıdır (Tablo 3). Diyabetik ayak ülserinde prognoza yönelik diyabetik ülser şiddet skoru (diabetic ulcer severity score -DUSS) tarif edilmiştir (Tablo 3).…”
Section: Di̇yabeti̇k Ayakta Genel Tedavi̇ şEmasiunclassified
“…SINBAD (Site-Ischemia-Neuropathy-Bacterial infection-Area-Depth) sınıflandırması [21] Ülserin CNO'nun klinik evrelemesi Eichenholtz tarafından yapılmıştır. [30] Evre 1 akut inflamatuvar dönemdir, radyografide kemiklerde parçalanma, eklemlerde çıkık görülür.…”
Section: Di̇yabeti̇k Nöropati̇unclassified